Fenologia do florescimento e características do perfume das flores de Passiflora quadrangularis L. (Maracujá-melão) - Montero, Daniel Antonio Villamil [UNESP]; Meletti, Laura Maria Molina; Marques, Marcia Ortiz Mayo (Lepidus Tecnologia, 2013)
Passiflora quadrangularis L. it’s a neotropical species, commonly known in Brazil as the melon passion fruit due to the size and format of its fruits. Currently, it has been widely disseminated throughout the tropics and it is commercially produced on a small scale, but mostly locally consumed because the fruits bruise easily when shipped. The plants of P. quadrangularis are vigorous climbers with abundant foliage and big beautiful scented flowers for which its use as ornamental plant seems particularly interesting. It has been stipulated that for the effective use of passion flowers in the ornamental plant market, studies need to be done on the flowering phenology. For this reason, we investigated some features regarding the flowering phenology and the composition of the scent produced by the flowers of P. quadrangularis cultivated at greenhouse. We present data concerning to the flowering period, blossom pick, relative blossom intensity and some characteristics of the flower scent. We conclude that P. quadrangularis represents a novel alternative as an ornamental plant in Brazil, because it’s abundant, big, scented, colorful, anthesis-simultaneous and flowers with long period of blossom. Also because it´s edible fruit and the medicinal properties of the exuberant foliage that could offer a nice shading for outdoor leisure areas and/or shade plants.

Passiflora quadrangularis L. é uma espécie originária do neotrópico, conhecida no Brasil como maracujá-melão devido ao tamanho e formato dos seus frutos. Tem sido amplamente disseminada nas regiões tropicais do mundo onde é produzida em pequena escala para comercialização dos frutos, o que ocorre bem próximo às regiões de cultivo, em função da dificuldade de conservação pós-colheita. As plantas são trepadeiras bastante vigorosas, com flores abundantes, grandes e perfumadas, o que amplia o seu valor e a torna particularmente interessante para caramanchões e cercas-vivas. O uso efetivo de passifloras no mercado de plantas ornamentais depende de estudos da fenologia floral. Neste trabalho foram estudadas algumas características da fenologia floral e o perfume das flores de P. quadrangularis, sob cultivo protegido. São apresentados os dados relativos ao período de floração, picos de florescimento e intensidade relativa das flores, bem como algumas características do perfume floral. Conclui-se que a espécie representa uma nova alternativa de cultivo para fins ornamentais, por apresentar múltiplas flores em antese simultânea, abundantes, grandes, fragrantes e coloridas, com longo período de floração no ano, além de frutos comestíveis, folhas exuberantes e medicinais que oferecem amplo sombreamento para áreas externas de lazer e/ou outras plantas cultivadas.
Keywords: Passifloraceae; Floral phenology; Ornamental; Floral scent; Passifloraceae; Badea; Ornamental; Fragrância floral